The Einstein Telescope standard siren simulations for f(Q) cosmologies - Xianfu Su; Dongze He; Yi Zhang (European Physical Journal C: Particles and Fields)
Abstract To investigate the model and extra frictional effects in standard siren simulation of f(Q) cosmologies, we simulated three types of standard siren data based on different fiducial models ( $$Λ $$ Λ CDM and f(Q) models). Both effects are important in standard siren simulation. Explicitly, the $$f(Q)_P$$ f ( Q ) P and $$f(Q)_E$$ f ( Q ) E models need more observational data (e.g. growth factor) to further study. The $$f(Q)_{PE}$$ f ( Q ) PE model could be ruled out by the EM data. And both the $$f(Q)_{HT}$$ f ( Q ) HT models will be excluded by the future standard siren data.